Entry Strategy of Bageteria to Polish Market - Bandíková, Miriam (2024)
The aim of this work is to develop a business plan that FIN needs to enter the Polish market. SWOT analysis, PESTLE analysis, a questionnaire from Polish respondents and an interview with a Polish businessman are used to achieve relevant results. The results of the research showed that this operation will be beneficial for the company, as the Polish respondents indicated that they would be interested in a company with a similar concept. Based on all the information obtained, it was found that it would be most advantageous for the company to use the direct exporting method, and if the operation is successful, the company would consider opening its own production plant in Poland.